Breeding honey bees (Apis mellifera L.) for low and high Varroa destructor population growth: Gene expression of bees performing grooming behavior - Morfin, Nuria; Harpur, Brock A.; De la Mora, Alvaro; Guzman-Novoa, Ernesto (Frontiers in Insect Science, 2023)
Social organisms, including honey bees (Apis mellifera L.), have defense mechanisms to control the multiplication and transmission of parasites and pathogens within their colonies. Self-grooming, a mechanism of behavioral immunity, seems to contribute to restrain the population growth of the ectoparasitic mite Varroa destructor in honey bee colonies. Because V. destructor is the most damaging parasite of honey bees, breeding them for resistance against the mite is a high priority of the beekeeping industry. We conducted a bidirectional breeding program to select honey bee colonies with low and high V. destructor population growth (LVG and HVG, respectively). Having high and low lines of bees allowed the study of genetic mechanisms underlying self-grooming behavior between the extreme genotypes. Worker bees were classified into two categories: ‘light groomers’ and ‘intense groomers’. The brains of bees from the different categories (LVG-intense, LVG-light, HVG-intense, and HVG-light) were used for gene expression and viral quantification analyses. Differentially expressed genes (DEGs) associated with the LVG and HVG lines were identified, including four odorant-binding proteins and a gustatory receptor. A functional enrichment analysis showed 19 enriched pathways from a list of 219 down-regulated DEGs in HVG bees, including the Kyoto Encyclopedia of Genes and Genomes (KEGG) term of oxidative phosphorylation. Additionally, bees from the LVG line showed lower levels of Apis rhabdovirus 1 and 2, Varroa destructor virus -1 (VDV-1/DWV-B), and Deformed wing virus-A (DWV-A) compared to bees of the HVG line. The difference in expression of odorant-binding protein genes and a gustatory receptor between bee lines suggests a possible link between them and the perception of irritants to trigger rapid self-grooming instances that require the activation of energy metabolic pathways. Therefore, our results provide new insights on the molecular mechanisms involved in honey bee grooming behavior. Differences in viral levels in the brains of LVG and HVG bees showed the importance of investigating the pathogenicity and potential impacts of neurotropic viruses on behavioral immunity. The results of this study advance the understanding of a trait used for selective breeding, self-grooming, and the potential of using genomic assisted selection to improve breeding programs.